Dental follicle mesenchymal stem cells down-regulate Th2-mediated immune response in asthmatic patients mononuclear cells - ÖZEN, AHMET OĞUZHAN; GÖKER, MEHMET KAMİL; AKKOÇ, TUNÇ (WILEY, 2018)
BackgroundAsthma is a chronic inflammatory disease in which inflammatory responses have the polarisation of CD4(+) T cells to Th2 cells. Dental follicle mesenchymal stem cells (DFSCs) have strong anti-inflammatory properties comparable to other mesenchymal stem cells. ObjectiveWe investigated the immunomodulatory effects of DFSCs on CD4(+) T helper cell responses of asthmatic patients and compared the results with those obtained with asthmatic subjects on immunotherapy and with healthy individuals. MethodPeripheral blood mononuclear cells (PBMC) were isolated from immunotherapy naive asthmatics, asthmatics on subcutaneous Der p1 immunotherapy and from healthy individuals. PBMC were pre-conditioned with anti-CD3/anti-CD28 mAbs, Der p1 or IFN- in the presence and absence of DFSCs and analysed for T cell viability and proliferation, CD4(+)CD25(+)FOXP3(+) regulatory T cell frequencies, cytokine expression, and GATA3, T bet and FoxP3 expressions. Neutralisation of TGF- and blockade of IDO and PGE2 pathways were performed to determine suppressive signalling pathways of DFSCs. ResultsDental follicle mesenchymal stem cells suppressed proliferative responses of CD4(+) T lymphocytes and increased the frequency of Treg cells. DFSCs decreased effector and effector memory CD4(+) T cell phenotypes in favour of naive T cell markers. DFSCs decreased IL-4 and GATA3 expression and increased IFN-, T-bet and IL-10 expression in asthmatics. Costimulatory molecules were suppressed in monocytes with DFSCs in the cocultures. DFSCs down-regulated inflammatory responses via IDO and TGF- pathways in asthmatic patients. ConclusionDental follicle mesenchymal stem cells suppressed allergen-induced Th2-cell polarisation in favour of Th1 responses and attenuated antigen-presenting cell co-stimulatory activities. These studies suggest that DFSC-based cell therapy may provide pro-tolerogenic immunomodulation relevant to allergic diseases such as asthma.
Keywords: asthma; dental follicle mesenchymal stem cells; house dust mite; immunomodulation; T-CELLS; IMMUNOMODULATION; IMMUNOTHERAPY; PHENOTYPES; ALLERGY; CD86